2018
DOI: 10.1111/str.12270
|View full text |Cite
|
Sign up to set email alerts
|

A procedure for high residual stresses measurement using the ring‐core method

Abstract: The ring‐core method is a mechanical technique used to determine the residual stresses on the surface of materials by milling a narrow circular groove around the point of interest and monitoring the strain variation. Original stress can be evaluated by using the relaxed strain through the linear elasticity theory. In case of a highly stressed field, the yielding of the material around the groove and its bottom causes an error related to the hypothesis of the basic theory of the method. In this paper, the plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It was also clarified that these errors are a function of the ring geometry, material properties, and maximum residual stress magnitude. [ 95 ] Bouffioux and teammates measured residual stresses on long‐rolled profiles conducting X‐ray diffraction (XRD), ring core (with strain gauges), and sectioning methods. They reported that the ring core measurement results agree with numerical models, both in longitudinal and in transverse directions, suggesting that this method is well adapted to this kind of piece.…”
Section: Determination Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also clarified that these errors are a function of the ring geometry, material properties, and maximum residual stress magnitude. [ 95 ] Bouffioux and teammates measured residual stresses on long‐rolled profiles conducting X‐ray diffraction (XRD), ring core (with strain gauges), and sectioning methods. They reported that the ring core measurement results agree with numerical models, both in longitudinal and in transverse directions, suggesting that this method is well adapted to this kind of piece.…”
Section: Determination Methodsmentioning
confidence: 99%
“…The residual stress response due to WEDM cutting is discussed in the study by Salvatti et al [232] Over recent decades, various destructive and nondestructive methods aimed at measuring the machining-induced surface, and internal residual stresses have been developed. Moharrami et al [95] utilized the ring core method to measure residual stress in the milling of narrow circular grooves in which the error value was lower than 1.5%. Chupakhin et al used the hole drilling method to study the effect of material behavior on the residual stress profile determination.…”
Section: Mechanicalmentioning
confidence: 99%